Llama Llama and friends! [videorecording (DVD)] - Dewdney, Anna (NCircle Entertainment, 2022)
Llama Llama springs to life in these heart-warming tales based on the award-winning book series by author and illustrator Anna Dewdney. Join Llama Llama, Nelly Gnu, Luna Giraffe, Euclid the Sheep, and Gilroy Goat as they explore their friendly hometown and make childhood memories.